Pelaksanaan Total Manajemen Mutu Terpadu Sebagai Upaya Meningkatkan Kualitas Pembelajaran - Maniar Naharti (Journal of Elementary School (JOES), 2020)
This study aims to determine the implementation of total integrated quality management in an effort to improve the quality of learning at SDN 010 Bengkulu Utara. This research is a school action research (School Action Research), because the research was conducted to solve the problem of the learning process in schools. This research will be conducted at SDN 010 North Bengkulu, Bengkulu Province. The research was conducted from January to March 2019. The research subjects were the entire board of teachers, employees and students from grades I to 6 at SDN 010 Bengkulu Utara. The results of the research are the implementation of total integrated quality management can improve the quality of learning at SDN 010 Bengkulu Utara, this can be seen from the final increase in the quality of learning in the planning program by 90%, implementation 95.85%, evaluation 87.5%, monitoring 93.75% and teacher performance increased 87.5%. Conclusion, Integrated total quality management is an activity that is interrelated between components with one another to form a network of functions, especially in classroom learning, and is proven to improve the quality of learning. Keywords: Implementation of Integrated Quality Management, Quality of Learning, Improvement of Learning Outcomes